Why Public Higher Education Should Be Free : How to Decrease Cost and Increase Quality at American Universities - Samuels, Robert, 1961- (Book collections on Project MUSE., 2013)
The author explains why universities cost so much and offers solutions as to how they can reduce their expenses by concentrating on their core mission of instruction and research. Not only can tuition be reduced, but public universities and colleges can be made free by allocating existing resources to provide quality undergraduate education and diminishing the amount of money spent in the areas of athletics, administration, and public research.